The Responsible rule of Media and Media Literacy in Strengthening Communal Harmony between Buddhists and Muslims in Thai Society - Mokesh Barua (STAB Kertarajasa, 2022)
Media as a potent tool and play an outstanding role to promote social, religious and communal harmony for the betterment of the society, the nation as well as the all humanity. Beside the communal disharmony and conflict are fueled by the fear, suspicion and hatred which frequently spread by transmission of different channels. Therefore, it is important to be aware of the media environment and to gain media literacy how the mass media operate and how they affect peaceful coexistence and religious tolerance in the society. Thailand is the religious diverse country of southeast Asia. Buddhism is the majority of Thailand yet other major world religion like Hinduism, Islam and Christianity are active and generally they can all be found living together in peace and harmony. Media plays a vital role to strengthening communal harmony between Buddhist and Muslim in Thai society. But frequently mass of media transmission conflicting news specially, southern part of Thailand where the relation between Buddhist and Muslim coming under going pressure. This paper will study the positive and negative impact of media on communal harmony between Buddhist and Muslim in Thai society. Moreover, it will study the importance of Media literacy to promoting peaceful coexistence in Thai society as well as Modern society.